ANALYSIS OF AIRCRAFT DELAYS AT THE STAGE OF ARRIVAL AT AIRPORT - Kharchenko, Volodymyr; Tapia, Kateryna (Proceedings of National Aviation University (archive), 2014)
Delays in arrival phase of flight depend on the manner in which airspace is organized, the application oftechnology and runway availability. Service process at the stage of arrival at airport is modeled. Service rate at airportthat has influence on waiting time for landing is analyzed.